Comparative analysis and structural modeling of elaeis oleifera FAD2, a fatty acid desaturase involved in unsaturated fatty acid composition of american oil palm - Ben Ayed, Rayda; Chirmade, Tejas; Hanana, Mohsen; Khamassi, Khalil; Ercisli, Sezai; Choudhary, Ravish; Kadoo, Narendra; Karunakaran, Rohini (Biology-Basel, 2022)
Simple Summary Palm oil has become the world's most important vegetable oil in terms of production quantity, and its overall demand is exponentially growing with the global population. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing palm oil quality. In this study, we focused on FAD2, a fatty acid desaturase enzyme involved in the desaturation and conversion of oleic acid to linoleic acid in Elaeis oleifera, identified through in silico annotation analysis. Our phylogenetic and comparative studies revealed two SNP markers, SNP278 and SNP851, significantly correlated with the oleic/linoleic acid contents. Our study provides fundamental insights into the mechanism of fatty acids synthesis in oil palm and could support the application of molecular biology techniques to enhance the enzymatic activity and substrate affinity of EoFAD2. American oil palm (Elaeis oleifera) is an important source of dietary oil that could fulfill the increasing worldwide demand for cooking oil. Therefore, improving its production is crucial and could be realized through breeding and genetic engineering approaches aiming to obtain high-yielding varieties with improved oil content and quality. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing oil quality. Our work focused on a fatty acid desaturase (FAD) enzyme involved in the desaturation and conversion of oleic acid to linoleic acid. Following the in silico identification and annotation of Elaeis oleifera FAD2, its molecular and structural features characterization was performed to better understand the mechanistic bases of its enzymatic activity. EoFAD2 is 1173 nucleotides long and encodes a protein of 390 amino acids that shares similarities with other FADs. Interestingly, the phylogenetic study showed three distinguished groups where EoFAD2 clustered among monocotyledonous taxa. EoFAD2 is a membrane-bound protein with five transmembrane domains presumably located in the endoplasmic reticulum. The homodimer organization model of EoFAD2 enzyme and substrates and respective substrate-binding residues were predicted and described. Moreover, the comparison between 24 FAD2 sequences from different species generated two interesting single-nucleotide polymorphisms (SNPs) associated with the oleic/linoleic acid contents.
Keywords: FAD2; Fatty acids; in silico annotation; linoleic acid ratio; oil palm; oleic; SNP; structural modeling

SNP discovery and structural insights into OeFAD2 unravelling high oleic/linoleic ratio in olive oil - Ben Ayed, Rayda; Moreau, Fabienne; Ben Hlima, Hajer; Rebai, Ahmed; Ercisli, Sezai; Kadoo, Narendra; Hanana, Mohsen; Assouguem, Amine; Ullah, Riaz; Ali, Essam A. (Computational and Structural Biotechnology Journal, 2022)
Fatty Acid Desaturase 2 (FAD2), a key enzyme in the fatty acid biosynthesis pathway, is involved in the desaturation and conversion of oleic acid to linoleic acid. Therefore, it plays a crucial role in oleic/linoleic acid ratio and the quality of olive oil. DNA sequencing of 19 FAD2 genes from a set of olive oil varieties revealed several single-nucleotide polymorphisms (SNPs) and highlighted associations between some of the SNPs and saturated fatty acids contents. This was further confirmed by SNP-interaction and machine learning approach. Haplotype diversity analysis led to the discovery of three highly polymorphic SNPs and four haplotypes harboring differential oleic/linoleic acid ratios. Moreover, a combination of molecular modeling and docking experiments allowed a deeper and better understanding of the structure-function relationship of the FAD2 enzyme. Sequence patterns and variations involved in the regulation of the FAD2 activity were also identified. Furthermore, S82C and H213N substitutions in OeFAD2 make the Oueslati variety more interesting in terms of fatty acid profile and oleic acid level. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology.
Keywords: docking; Fatty acid desaturase; Haplotype; machine learning; Oleic/linoleic acid ratio; Protein structure